New horizons for female birdsong : evolution, culture and analysis tools : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Ecology at Massey University, Auckland, New Zealand - Webb, Wesley (Massey University, 2020)
As a result of male-centric, northern-hemisphere-biased sexual selection theory, elaborate female traits in songbirds have been largely overlooked as unusual or non-functional by-products of male evolution. However, recent research has revealed that female song is present in most surveyed songbirds and was in fact the ancestral condition to the clade. Additionally, a high proportion of songbird species have colourful females, and both song and showy colours have demonstrated female-specific functions in a growing number of species. We have much to learn about the evolution and functions of elaborate female traits in general, and female song in particular. This thesis extends the horizons of female birdsong research in three ways: (1) by revealing the broad-scale evolutionary relationship of female song and plumage elaboration across the songbirds, (2) by developing new accessible tools for the measurement and analysis of song complexity, and (3) by showing—through a detailed field study on a large natural metapopulation—how vocal culture operates differentially in males and females. First, to understand the drivers of elaborate female traits, I tested the evolutionary relationship between female song presence and plumage colouration across the songbirds. I found strong support for a positive evolutionary correlation between traits, with female song more prevalent amongst species with elaborated female plumage. These results suggest that contrary to the idea of trade-off between showy traits, female plumage colouration and female song likely evolved together under similar selection pressures and that their respective functions are reinforcing. Second, I introduce new bioacoustics software, 𝘒𝘰𝘦, designed to meet the need for detailed classification and analysis of song complexity. The program enables visualisation, segmentation, rapid classification and analysis of song structure. I demonstrate 𝘒𝘰𝘦 with a case study of New Zealand bellbird 𝘈𝘯𝘵𝘩𝘰𝘳𝘯𝘪𝘴 𝘮𝘦𝘭𝘢𝘯𝘶𝘳𝘢 song, showcasing the capabilities for large-scale bioacoustics research and its application to female song. Third, I conducted one of the first detailed field-based analyses of female song culture, studying an archipelago metapopulation of New Zealand bellbirds. Comparing between male and female sectors of each population, I found equal syllable diversity, largely separate repertoires, and contrasting patterns of sharing between sites—revealing female dialects and pronounced sex differences in cultural evolution. By combining broad-scale evolutionary approaches, novel song analysis tools, and a detailed field study, this thesis demonstrates that female song can be as much an elaborate signal as male song. I describe how future work can build on these findings to expand understanding of elaborate female traits.
Published papers appear in Appendix 7.1. and 7.2 respectively under a CC BY 4.0 and CC BY licence: Webb, W. H., Brunton, D. H., Aguirre, J. D., Thomas, D. B., Valcu, M., & Dale, J. (2016). Female song occurs in songbirds with more elaborate female coloration and reduced sexual dichromatism. Frontiers in Ecology and Evolution, 4(22). https://doi.org/10.3389/fevo.2016.00022 Yukio Fukuzawa, Wesley Webb, Matthew Pawley, Michelle Roper, Stephen Marsland, Dianne Brunton, & Andrew Gilman. (2020). Koe: Web-based software to classify acoustic units and analyse sequence structure in animal vocalisations. Methods in Ecology and Evolution, 11(3). https://doi.org/10.1111/2041-210X.13336
Keywords: Birdsongs; Songbirds; Behavior; Color; Korimako; New Zealand; Sexual dimorphism (Animals); 310405 Evolutionary ecology